(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article has been written from the story which was told by Uzbek writer Normurad Norkobilov, who made an interesting expedition to the unexplored cave “Peshigor”, which situated in Zaamin district of Uzbekistan. There too many authors whose stories were written about nature, for example as well-known American naturalist author Ernest Seton Thomson who created thousand stories about animalistic genre by travelling Wildlife of nature or Jack London , Murrey Abraham, Sidonie-Gabrielle Colette ei. There are many honorable naturalist authors in Uzbekistan, such as, Tog’ay Murod, Gofur Gulom, Abdulla Qodiriy, Shukur Xolmirzayev, Normurod Norkobilov ei. Normurod Norkobilov is an Uzbek writer who gives the motivation from nature to create his amazing stories, he made thousand expeditions, his love to the nature pushed up him to research every inch of the motherland. His stories are connected with the realistic wild and domestic natural life. In this article we can get an information which happened during the expedition. There were many interesting accidents, unforeseen circumstance. And the main fact that they found an ancient building inside the cave.